Stroke in the state of Alagoas, Brazil: a descriptive analysis of a northeastern scenario - Letícia Januzi de Almeida Rocha; Kauan Araújo da Silva; Arthur de Lima Chagas; Arthur de Oliveira Veras; Vitor Gustavo Leão Souto; Maria Clara Motta Barbosa Valente; Jussara Almeida de Oliveira Baggio (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background There is little information available on stroke epidemiology in the northeast of Brazil. Objective Our objective was to investigate the prevalence of the stroke subtypes, prevalence of cerebrovascular risk factors and patterns of management in a public neurovascular outpatient referral service, in Alagoas. Methods Data were prospectively collected from consecutive patients with stroke who were treated in a specialized neurovascular clinic between November 2016 and June 2018. Recurrence was evaluated by telephone 12 months after patients had been included in the study. Results We evaluated 190 patients (mean age, 60.22 ( 13.29 years; 60.5% males). Ischemic stroke was the most frequent subtype (85.2%). Sedentary lifestyle was the most common risk factor (71.6%), followed by hypertension (62.6%) and stroke family history (41.1%). Only 21.5% of the patients were transported by ambulance to the hospital, and 42.6% received medical support in hospital units or emergency units with no imaging support. The median NIHSS was 2.5 (IQR, 1-5) and mRS was 2 (IQR, 1-3). We found a high rate of undetermined stroke (35.8%), and few patients completed the etiological investigation. One year after inclusion in the study, 12 patients (6.3%) had died and 14 (7.3%) had had another stroke. Conclusions The prevalence of cerebrovascular risk factors and clinical presentation were similar to what had been seen in previous series. A notable number of patients received medical support in institutions with no imaging equipment. The high number of cases of undetermined stroke etiology shows the difficulty in accessing healthcare services in Alagoas.